Comparative Anthropometric Study about Growth in Head and Skeleton between Children with Autism Spectrum Disorder and Normal Children of Bangladesh - Sohel, Md Ibrahim; Ashrafuzzaman, Md; Mostafa, Asma; Hossain, Mohammad Monir; Kibria, Md Anwarul (IAHS Medical Journal, 2022)
Background: A child grows in various ways like physical, mental, emotional, social and cultural growth. Physical, mental and social developments are influenced by nutrition. Body composition is strongly associated with nutritional status, specific diet, physical exercise, diseases and genes. The determination of body composition allows for the quantitative assessment of muscle mass and adiposity changes that reflects nutritional intake, losses and expenses over a time period. Thus, the present study was carried out to measure the head circumference, mid arm circumference, waist circumference and mid-thigh circumference of children with autism spectrum disorder and to evaluate if there is any significant difference with normal children of Bangladesh. The outcome of the study would be helpful for further research work to establish brain growth, assessment of growth and comparison between children with autism spectrum disorder and normal Children in Bangladesh. Materials and methods: It was cross-sectional and observational study. The study population was Group A consists of 100 normal Bangladeshi children and Group B consists of 100 Bangladeshi children with Autism spectrum disorder, aged between 02 and 18 years collected by convenient sampling. Four variables namely head circumference, mid arm circumference, waist circumference and midthigh circumference were analyzed in this study. Results: Children with autism spectrum disorder had statistically significant lower head and mid thigh circumference; mid arm and waist circumference had statistically non-significant. Conclusion: The results of this study provide the baseline information about assessment of brain growth and nutritional growth of muscles mass of normal children and children with autism spectrum disorder in Bangladesh which will help to monitor brain & nutritional growth of children. IAHS Medical Journal Vol 4(1), June 2021; 33-37